Scandinavian literature from Brandes to our day - Topsøe-Jensen, Helge Gottlieb 1896-1976 (Scandinavian classics, 1929)
Introductory survey -- I. The modern awakening. Denmark ; Norway -- II. Naturalism. Denmark ; Norway ; Sweden -- III. Neo-romanticism and symbolism. Denmark ; Norway ; Sweden -- IV. New currents, 1900-1914. Denmark ; Norway ; Sweden -- V. Conclusion